Carcharhinus altimus ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Carcharhinus altimus (Springer, 1950). Bignose Shark. 3.0 m (9.8 ft) TL (Compagno et al. in Fischer et al. 1995). Circumglobal; patchily distributed from central Baja California (Compagno et al. in Fischer et al. 1995) to northern Peru (Chirichigno and Vélez 1998), including Gulf of California (Compagno et al. in Fischer et al. 1995), and Islas Galápagos (Grove and Lavenberg 1997). Depth: surface to 810 m (2,633 ft) (min.: Compagno in Carpenter and De Angeles 2016; max.: Weigmann 2016). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 17, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...